INVESTIGATING THE IMPACT OF RAPID RESPONSIVENESS PRESS TOOL MANUFACTURING SYSTEMS ON SOUTH AFRICAN LABOUR PRODUCTIVITY - Phuluwa, Humbulani Simon (International Journal of Industrial Engineering: Theory, Applications and Practice, 2018)
Manufacturing responsiveness in today’s world of global competition is essential for competing and also in meeting both customer expectations and demands. Business enterprises such as press tool enterprises, are facing challenges ranging from ineffective manufacturing systems to rigid labour regulations. The effectiveness and efficiency of changeovers with respect to manufacturing facilities, set up and process flow from one product to another, is critical for increased flexibility and responsive manufacturing. However, much has been said about system responsiveness towards planned targets and deliverables, but little research has explored the impact that responsiveness has on labour productivity. This study investigates and reviews literature on responsiveness to determine the links with labour productivity. A survey was conducted focusing on press tool industries located in Gauteng, South Africa, since the majority of manufacturing enterprises are located in this province. The overall objective of the study is to understand the critical elements that press tool industries should be aware of when rapid response systems are applied and the impact of these systems on labour productivity. A conceptual model is thus proposed to optimize the labour productivity on a shop floor. The conclusion of the study was that Reconfigurable Management Systems principles should be implemented in the broad press tool industry with the aim of revitalising labour productivity, competiveness and sustainability of these businesses. Further study will be focusing on how to optimise labour productivity in a rapid response environment.